Phylogenetic Study of Selected Species of Starlings and Pies Inferred from Partial Mitochondrial DNA Cytochrome Oxidase I (COI) Gene - Soh Hui, Teng (Universiti Malaysia Sarawak (UNIMAS), 2009)
In this study, the phylogenetic relationship of selected species of starlings and pies were determined by using partial mitochondrial DNA COI gene. Four species of 11 individuals comprising of genera Cissa, Aplonis, Gracula and Acridotheres were included in this phylogenetic study. DNA was extracted from tissue samples following the DNA extraction protocol. The annealing temperature for these selected species ranges from 50 °C to 52 °C. This study examines 493 base pairs of the mitochondrial DNA cytochrome oxidase I sequences from 11 individuals. The phylogenetic relationship was analyzed using Phylogenetic Analysis Using Parsimony PAUP (version 4.0). Phylogenetic trees were constructed using neighbor - joining (NJ), maximum parsimony (MP) and maximum likelihood (ML) methods. The three phylogenetic trees show similar topology but slightly different bootstrap values. MP tree shows the most suitable tree to illustrate the differences between the two families. Common myna (Acridotheres tristis) formed the basal Glade with Asian glossy starling (Aplonis panayensis) and hill myna (Gracula religiosa) for MP trees.